P. Teilhard de Chardin’s Christian Evolutionism - Kuzmickas, Bronislavas (Problemos, 1971)
The paper provides a critical account of the evolutionistic conception of the French catholic philosopher, scientist and paleoanthropologist P. Teilhard de Chardin. Spreading of Teilhardism in capitalist countries can be explained by the originality or some of its ideas and, on the other hand, by changes occurring in modem Catholicism. P. Teilhard de Chardin endeavours to modernize the religious world outlook with the view of adapting it to the data or contemporary science, to the ideas of social progress and humanism. P. Teilhard de Chardin tries to unite the idea or the self-development of the world with that of the creation of the world out of nothing. The author discloses the main points or inconsistency of Teilhardism and demonstrates the impossibility of harmony between the scientific and religions world conceptions.